2007
DOI: 10.1159/000107944
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetic Change of the Serum Angiogenin Level in Patients with Acute Cerebral Infarction

Abstract: Serum angiogenin (ANG) levels were measured with ELISA in 30 cerebral infarction patients at different time points (within 48 h and on days 3, 7 and 14 after onset of cerebral infarction) and in 20 control subjects. Serum ANG levels in patients were 415.1 ± 76.8, 410.6 ± 82.1, 443.6 ± 91.1 and 395.3 ± 83.9 ng/ml within 48 h and on days 3, 7 and 14 after cerebral infarction, respectively. Serum ANG level in control group was 334.9 ± 93.9 ng/ml. Serum ANG levels were significantly higher in patients with cerebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
3
9
0
Order By: Relevance
“…Certain patterns of change present after SCI in our sample population could potentially have been masked by this great inter-individual variation, as it would be logistically impossible to acquire a non-SCI baseline measure for each SCI patient enrolled in this study to use as a comparison for their post-SCI expression values. However, a majority of the values recorded for our non-SCI controls reflect the values of controls which have previously been reported (Table 3) [6, 29, 31, 68, 80, 84, 95, 98, 101, 103, 112, 138, 140, 141, 152, 157, 174, 192]. …”
Section: Changes In Angiogenic Proteins After Acute Human Scisupporting
confidence: 77%
“…Certain patterns of change present after SCI in our sample population could potentially have been masked by this great inter-individual variation, as it would be logistically impossible to acquire a non-SCI baseline measure for each SCI patient enrolled in this study to use as a comparison for their post-SCI expression values. However, a majority of the values recorded for our non-SCI controls reflect the values of controls which have previously been reported (Table 3) [6, 29, 31, 68, 80, 84, 95, 98, 101, 103, 112, 138, 140, 141, 152, 157, 174, 192]. …”
Section: Changes In Angiogenic Proteins After Acute Human Scisupporting
confidence: 77%
“…Angiogenin has also been studied in cardiovascular diseases showing an increase in blood in chronic heart failure or in acute coronary syndrome in association with severity or prognosis ( 51 , 52 ). In the context of stroke, Huang et al reported that higher serum angiogenin levels within the first week after stroke are associated with larger infarct size ( 53 ). This up-regulation of angiogenin in the acute phase of cardiovascular diseases has also been observed in our study by identifying angiogenin in neurons or vessels of the brain within the first 4 days in infarcted areas.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of IL-1, IL-2 and TNF-α in the culture liquid of peritoneal macrophage were measured by radioimimunoassay according to the manufacturer's instructions (Zhang et al 2008). The kits of the three cytokines were produced by Beijing Huaying Institute of Biotechnology and the detecting instrument was GC-911-γ-radioimmunity arithmometer.…”
Section: Determination Of Cytokinesmentioning
confidence: 99%